Persepsi Perserta Ekstrakurikuler Bola Basket SMP Negeri 1 Lemahabang - Muliawati, Intan Dwi; Mahardhika, Dhika Bayu; Achmad, Irfan Zinat (Peneliti.net, 2023)
The problem of this research is that it is not yet known how the participants perceive basketball extracurricular activities in junior high schools. The aim of this research is to find out how the Perceptions of Junior High School Basketball Extracurricular Participants are. The survey is the method used in this study and uses a quantitative approach. The samples used were 52 students using probability sampling technique using simple random sampling. The data collection technique used in this study was a survey technique, using a questionnaire by distributing questionnaires received by basketball extracurricular participants. From the results of this study it was known that the basketball extracurricular participants were